A group III patatin-like phospholipase gene pPLAIIIδ regulates lignin biosynthesis and influences the rate of seed germination in Arabidopsis thaliana - Simiyu, David Charles; Jang, Jin Hoon; Lee, Ok Ran (Frontiers in Plant Science, 2023)
The lignification of plant secondary walls is an important process that provides plants with mechanical support. However, the presence of lignin in the secondary walls affects the readily availability of cellulose required in various industries, including the biofuel, paper, and textile industries. Thus, plants with less lignin are ideal for usage in such industries. Molecular studies have identified genes that regulate plant lignification, including group III genes of plantspecific patatin-related phospholipases genes. Recent studies have reported decreased lignin content when pPLAIIIα, pPLAIIIγ (from Arabidopsis thaliana), and pPLAIIIβ (from Panax ginseng) were overexpressed in Arabidopsisshown that the overexpression of Arabidopsis thaliana genes pPLAIIIα and pPLAIIIγ and a Panax ginseng pPLAIIIβ has resulted in less lignin content in Arabidopsis. However, the role played by a closely related gene pPLAIIIδ in lignin biosynthesis has not yet been reported. In this study, we found that overexpression of the pPLAIIIδ significantly reduced the lignin content in secondary cell walls, whereas the silencing of the gene increased its secondary walls lignification. Transcript level analysis showed that the key structural and regulatory genes involved in the lignin biosynthesis pathway decreased in overexpression, and increased in RNAi plants with silenced pPLAIIIδ. Further analysis revealed that pPLAIIIδ played an influential role in several physiological processes including seed germination, and chlorophyll accumulation. Moreover, the gene also influenced the size of plants and plant organs, including leaves, and seeds, and root hairs. Generally, our study provides important insights toward the use of genetic engineering for lignin reduction in plants and provides information about the agronomical and physiological suitability of pPLAIIIδ transgenic plants for utilization in biomass processing industries.